Edukasi Penerapan Terapi Uap Sederhana dengan Minyak Kayu Putih di Posyandu Desa Karang Malang Puskesmas Gribig Kudus - Alvi Ratna Yuliana; Luluk Cahyanti; Vera Fitriana; Hirza Ainin Nur (Institut Teknologi dan Bisnis Semarang, 2024)
This community service activity aims to provide education about the application of simple steam therapy with eucalyptus oil at the Karang Malang Village Posyandu, which is located in the Gribig Health Center area, Kudus. Steam therapy is one of the effective traditional treatment methods in relieving symptoms of respiratory disorders such as flu, cough, and cold. Eucalyptus oil was chosen because of its eucalyptol content which functions as a natural decongestant. The methods used in this activity include counseling and direct demonstrations to mothers who have children under five at the Posyandu. The educational material covers the benefits of steam therapy, how to make and use it, and the safety measures that must be considered. The results of this activity showed that participants understood the benefits and how to apply simple steam therapy with eucalyptus oil, and were able to apply it at home. This activity also succeeded in raising awareness of the importance of safe and effective traditional medicine in family health care. The conclusion of this activity is that education and live demonstrations are effective methods in improving people's knowledge and skills about simple steam therapy. The recommendation for the next activity is to expand the scope of this education to other villages and involve more health cadres to ensure the sustainability of the program.